Legal Protection of Consumers (Heirs) for Rejection of Life Insurance Claims (Case Study of Supreme Court Decision No. 241 PK/Pdt/2011) - Edgar Thomas Butar-butar; Janpatar Simamora; Ria Juliana Siregar (PT FORMOSA CENDEKIA GLOBAL, 2025)
Life insurance is an agreement that binds the insurer and the insured to provide protection against risks that may occur, such as death. This study discussthe procedure for claiming life insurance and legal protection for consumers, especially heirs, in the context of Supreme Court Decision No. 241 PK/Pdt/2011. In the case, the claim filed by the heirs was rejected by PT. Sequis Life Insurance for reason that are considered invalid. This writing uses the normative juridical resaerch method, which is research conducted by researching literature and legal materials thar require secondary data as the main data. The study highlights the importance of a systematic claim procedure, which includes the collection of documents and the stages that must be followed. In addition, consumer legal protection is regulated in the Consumer Protection Act, which supports the rights of policyholders. The conclusion of the study shows that the rejection of claims that do not meet legal obligations can be detrimental to consumers, anf insurance companies must be in good faith and comply with applicable regulations to protect customer rights.